'Different isn't free': Gender @ work in a digital world. (September 2018) - Carrigan, Coleen
US society is thoroughly computerized and the majority of its population engages in activities involving computers. Why, then, does computer science and engineering (CSE) remain highly male-dominated and seemingly impervious to desegregation? This study explores how CSE professionals in corporations and universities navigate and subvert male hegemony to persist. I document practices in CSE that reproduce the ideological union between masculinity and competency, including hazing, bragging, and bullying. These practices, much like rites of passage, also serve to indoctrinate CSE workers to the core values in computing knowledge production, including constant observation, combative work styles, and male hegemony, all of which differentially impact women. Women who persist in CSE describe their experiences as wearisome, constrained by a fear of being different, and thus further marginalized. I argue that processes and value systems by which people become computing professionals reflect a gendered, technocratic culture, one that reproduces labor segregation in CSE.